CUSTOMERS’ SATISFACTION WITH THE UNIVERSITY NEW APPROACHES AND RESULTS - Valentina A. Ivashova; Evgeniy V. Galeev; Tatiana V. Fed’Kova (Высшее образование в России, 2016)
The article focuses on the tools which can be used for the University effective response to the modern challenges such as constantly changing quality characteristics of customers namely the differences in the educational level and socio+ psychological characteristics of the entering contingent; diverse motives in addressing to the University services, and divergent career plants of different customer groups; multi+level character of customers’ social and professional status. The introduction and development of the socio-cultural area gives the University an opportunity to overcome the key social challenges and to gain advantages in obtaining customers’ loyalty.